PKM Peningkatan Pengetahuan dan Keterampilan Ibu Rumah Tangga melalui Bimbingan Teknis Pengolahan Keripik Pisang Kepok - Rahma Sari Siregar; Retna Astuti Kuswandari; Rika Fitri Ilvira (Universitas Medan Area, 2023)
Housewives are increased to increase family income through the processing of kepok bananas, banana chips. Banana chips are banana chips that are popular and loved by all people. This activity aims to improve the knowledge and skills of housewives in processing banana chips, methods of implementing community service through material presentation and technical guidance for making banana chips. The presentation material was delivered by the PKM Implementation Team. As for the material that will be discussed in banana cultivation, analysis in the banana business. The next method is training in making banana chips, which is in accordance with the quality criteria determined by the Hijrah Banana Chips UMK. Participants who took part in this activity consisted of 19 housewives who live in Percut Sei Tuan District. The analysis technique was carried out through a questionnaire that was given to each participant. Questionnaires were given before and before the implementation of the activity. The results of the questionnaire were then recapitulated and presented in a descriptive form. The results of the activity showed an increase in the knowledge of each participant who attended the technical guidance activity for banana chips processing